A NEED ANALYSIS OF TASK ACTIVITY IDENTIFIED FOR TOURISM STUDENTS IN LISTENING AND SPEAKING INTEGRATED SKILL - Salzu Clarisa; Fauzi Miftakh; Maya Rahmawati (STKIP Siliwangi, 2022)
Task activity is part of learning to enhance the improvement students’ skill, especially integration skills of listening and speaking. However, many researchers have identified task activity and integration skill separately. This descriptive research focuses on identifying three aspects of need analysis such as Target Situation Analysis (TSA), Present Situation Analysis (PSA), and Learning Situation Analysis (LSA). The aim of this research is to find out appropriate task activity and materials based on students’ experiences learning in listening and speaking integrated skills. Data collection used interview from four tourism students, and analyzed English and major specific syllabus. The result of this study indicates that English lesson should adapt materials in major specific lesson, because materials affected to find suitable listening and speaking integrated task activity. The underlined result of this research is task activity can increase with new strategy and instruction which consider to previous learning, students’ lack, and students’ necessities. Implication need analysis showed listening and speaking integrated task activity is important to apply in English vocational school to achieve learners’ target skill.